Brain and culture : neurobiology, ideology, and social change - Wexler, Bruce E. (MIT Press, 2006)
"Brain and Culture reviews extensive neuroscience, psychological, social science, and historical research to offer a new view of the relationship between people and their environments. Our brains require sensory input from the environment to develop normally, and that input shapes the brain systems necessary for perception, memory, and thinking. Environmental shaping of the brain is much greater in people that in other animals and, more importantly, we shape the environment that shapes our brains to an extent without precedent. Even the structure and function of DNA that codes for brain proteins are changed by early life experience. Through these processes our brains shape themselves to the individual cultural and interpersonal environments in which we are reared."--Jacket